Holistic Evaluation of the Gut Microbiota through Data Envelopment Analysis: A Cross-Sectional Study - Taizo Matsuki; Sho Nakamura; Minami Nishiyama; Hiroto Narimatsu (Current Developments in Nutrition)
Background: The gut microbiome plays a crucial role in human health, but maintaining a healthy gut microbiome remains challenging. Current approaches often focus on individual components rather than providing a holistic assessment. Objectives: To introduce and evaluate a novel approach using data envelopment analysis (DEA) for assessing gut microbiota efficiency and identifying potential targets for personalized interventions. Methods: We conducted a cross-sectional analysis of 577 participants from the Kanagawa “ME-BYO” Prospective Cohort Study. Lifestyle factors and gut microbiota composition were assessed. DEA was employed to calculate an efficiency score for each participant, incorporating multiple inputs (lifestyle factors) and outputs (gut microbiotas). This score represents how efficiently an individual’s lifestyle factors contribute to their gut microbiota composition. Tobit regression analysis was used to assess associations between efficiency scores and demographic and health-related factors. Results: The mean efficiency score was 0.86, with 14.2% of participants classified as efficient. Efficiency scores showed positive correlations with alcohol intake and Faith's phylogenetic diversity. Tobit regression analysis revealed significant associations between efficiency scores and sex, fat intake, and yogurt consumption. DEA identified specific targets for improving gut microbiota composition in inefficient individuals. Conclusions: This study demonstrates the potential of DEA as a tool for evaluating gut microbiota efficiency and providing personalized recommendations for microbiota optimization. This approach could lead to more effective strategies for optimizing gut health across diverse populations.